2021
DOI: 10.9734/jpri/2021/v33i42a32396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Force Decay between Coil Spring, Elastomeric Chain and Tie-backs in Various Alcohol Concentrations found in Mouth Rinse: An In-vitro Study

Abstract: Background: The ability to close space efficiently in Orthodontics is of major clinical importance. Elastomeric power chain, coil spring, and tiebacks are commonly used in Orthodontics to achieve tooth movement during the closure of spaces. Many mouth rinses which are used by the patients to achieve good oral hygiene affect the properties of the material used during treatment resulting in force decay if they contain alcohol. Aim: To know the effect of mouth rinses containing different alcohol Concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…the authors reported that tie-backs have less strength decay when exposed to alcohol present in mouthwashes compared to elastomeric chain. 16 In order to ensure this study's reliability, we also checked the effectiveness of our closed elastomeric chain of 3M UNITEK, which based on different studies, has been endorsed as the golden standard of chains in orthodontics. 17 As mentioned above, the deformation of the elastomeric chain (3M UNITEK ©) used in our study was 46.58%.…”
Section: Discussionmentioning
confidence: 99%
“…the authors reported that tie-backs have less strength decay when exposed to alcohol present in mouthwashes compared to elastomeric chain. 16 In order to ensure this study's reliability, we also checked the effectiveness of our closed elastomeric chain of 3M UNITEK, which based on different studies, has been endorsed as the golden standard of chains in orthodontics. 17 As mentioned above, the deformation of the elastomeric chain (3M UNITEK ©) used in our study was 46.58%.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of proper clinical trials means many recommendations are based on indirect comparisons and anecdotic experiences. 16 Current guidance recommends that a tricyclic antidepressant or antiepileptic drug, gabapentin or pregabalin, should be the first-line choice for the pharmacological treatment of neuropathic pain of most causes. 14,29 In the absence of solid evidence of the predominance of one drug over another, it would seem practical to use the lowest-cost medicines first.…”
Section: Discussionmentioning
confidence: 99%
“…11.12. [14][15][16][17] Depending on the author of the entity, the first-line medication may switch to TCAs.…”
Section: Moderate To Severementioning
confidence: 99%